The Effect of Prior Term Birth on Risk of Recurrent Spontaneous Preterm Birth - Purisch, Stephanie E.; Turitz, Amy L.; Elovitz, Michal A.; Levine, Lisa D. (American Journal of Perinatology, 2018)
Objective The objective of this study was to evaluate the effect of prior term birth on recurrent spontaneous preterm birth (sPTB) risk.Study Design Retrospective cohort study of 211 women with prior sPTB, comparing women with and without prior term births. The primary outcome was recurrent sPTB <37 weeks. Analyses stratified by gestational age of prior sPTB and adjusted for confounders using multivariable logistic regression.Results The overall sPTB rate was 33.7%, with no statistical difference between women with and without prior term births (28.9 vs. 37.7%, p = 0.2). Among women with prior second-trimester loss (16–236/7 weeks), those with a term birth had a decreased sPTB rate (15.4 vs. 43.2%, p = 0.02), which persisted after adjusting for age and 17-α hydroxyprogesterone caproate use. For women with prior sPTB ≥24 weeks, there was no difference in sPTB with and without prior term births (29.5 vs. 26.6%, p = 0.7). A term birth as the most recent delivery lowered, but did not eliminate, the sPTB risk (19.1 vs. 36.4%, p = 0.1).Conclusion Prior term birth lowers the risk of recurrent sPTB for women with prior second-trimester loss, but not for women with prior sPTB ≥24 weeks. Women with prior preterm and term births should be counseled accordingly and all sPTB prevention strategies should be recommended.
Keywords: birth order; prematurity; recurrent preterm birth; spontaneous preterm birth